Identification of dropout predictors to a community-based physical activity programme that uses motivational interviewing. (17th November 2018) - Wade, Matthew; Brown, Nicola; Dancy, Bernadette; Mann, Steven; Gissane, Conor; Majumdar, Anne
Abstract: Background: Participant dropout reduces intervention effectiveness. Predicting dropout has been investigated for Exercise Referral Schemes, but not physical activity (PA) interventions with Motivational Interviewing (MI). Methods: Data from attendees ( n = 619) to a community-based PA programme utilizing MI techniques were analysed using a chi-squared test to determine dropout and attendance group differences. Binary logistic regression investigated the likelihood of dropout before 12 weeks. Results: A total of 44.7% of participants dropped out, with statistical ( P < 0.05) differences between groups for age, PA and disability. Regression for each variable showed participants aged 61–70 years (OR = 0.28, CI = 0.09–0.79; P = 0.018), >70 years (OR = 0.30, CI = 0.09–0.90; P = 0.036), and high PA (OR = 0.40, CI = 0.20–0.75; P = 0.006) reduced dropout likelihood. Endocrine system disorders (OR = 4.24, CI = 1.19–19.43; P = 0.036) and musculoskeletal disorders (OR = 3.14, CI = 1.84–5.45; P < 0.001) increased dropout likelihood. Significant variables were combined in a single regression model. Dropout significantly reduced for 61–70 years old (OR = 0.31, CI = 0.10–0.90; P = 0.035), and high PA (OR = 0.39, CI = 0.19–0.76; P = 0.008). Musculoskeletal disorders increased dropout (OR = 2.67, CI = 1.53–4.75; P < 0.001). Conclusions: Age, PA and disability type significantly influence dropout at 12 weeks. These are the first results specific to MI based programmes indicating the inclusion of MI and highlighting the need for further research.